FAMILY NUCLEUS IN THE EDUCATIONAL PROCESSES OF LANGUAGE AND LITERATURE IN ADOLESCENTS WITH DISABILITIES - Moreta Ruperti , Alejandra Margarita; Muñoz Verduga, Dolores Esperanza (Revista Minerva, 2023)
This work aimed to contribute to the improvement of the quality of education in adolescents with disabilities in Ecuador through the study of educational processes for language and literature from the review of specialized publications on this topic, through the review resorts to the meta-analysis of 78 articles published in scientific journals of Scopus, Scielo, Latindex databases, among others. The results regarding the inconsistencies in the institutions, the differences between ordinary education and special education are considered; however, the educational supports acquire greater significance in the promotion of self-determination. In short, the strategies used in the classroom and the individualized supports influence the self-determination of this group (Blázquez, Calvo, & Orgaz, 2021). It is concluded that in the development of the educational processes that condition the teacher, it is observed that the four knowledge of education are developed and therefore there is no integration that brings together the institution, the family and the community.